2009
DOI: 10.1093/cercor/bhp274
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 Viral Protein Tat Increases Glutamate and Decreases GABA Exocytosis from Human and Mouse Neocortical Nerve Endings

Abstract: Human immunodeficiency virus-1 (HIV-1)-encoded transactivator of transcription (Tat) potentiated the depolarization-evoked exocytosis of [(3)H]D-aspartate ([(3)H]D-ASP) from human neocortical terminals. The metabotropic glutamate (mGlu) 1 receptor antagonist 7-(hydroxyimino)cyclopropa[b]chromen-1a-carboxylate ethyl ester (CPCCOEt) prevented this effect, whereas the mGlu5 receptor antagonist 2-methyl-6-(phenylethynyl) pyridine hydrochloride (MPEP) was ineffective. Western blot analysis showed that human neocort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 50 publications
4
48
0
Order By: Relevance
“…The data demonstrated that the mGlu1/5 receptor agonist facilitated the 12 mM K + -evoked production of endogenous IP 3 and that this facilitation was significantly prevented by CPCCOEt. This is consistent with the participation of the mGlu1-induced signaling in the overproduction of the intraterminal second messenger (Musante et al, 2010). Thus, mGlu1 autoreceptors in mouse cortical nerve endings are positively coupled to an enzymatic pathway leading to IP 3 overproduction and the consequent release of Ca 2+ ions from intraterminal stores.…”
Section: Mglu1 Autoreceptors In Central Nervous Systemsupporting
confidence: 89%
“…The data demonstrated that the mGlu1/5 receptor agonist facilitated the 12 mM K + -evoked production of endogenous IP 3 and that this facilitation was significantly prevented by CPCCOEt. This is consistent with the participation of the mGlu1-induced signaling in the overproduction of the intraterminal second messenger (Musante et al, 2010). Thus, mGlu1 autoreceptors in mouse cortical nerve endings are positively coupled to an enzymatic pathway leading to IP 3 overproduction and the consequent release of Ca 2+ ions from intraterminal stores.…”
Section: Mglu1 Autoreceptors In Central Nervous Systemsupporting
confidence: 89%
“…In support of this notion, CSF levels of glutamate are fivefold greater in HIV+ individuals than in healthy controls 137 , and recent studies of HIV+ patients who received CART revealed selective increases in CSF levels of glutamate in patients with HAND compared with patients without neurocognitive impairment 74 . Tat and envelope glycoprotein gp120 have been shown to decrease glial and synaptic glutamate uptake 138,139 , stimulate glutamate release from nerve endings 138,140 , and phosphorylate glutamate receptors, thus potentiating the toxicity of the neurotransmitter 141 . Although glutamate levels in the CSF are increased in HIV+ patients with cognitive impairment, glutamate levels are selectively lower in the parietal grey matter, basal ganglia and cortex 77,78 .…”
Section: Pathogenesis In Handmentioning
confidence: 99%
“…Tat promotes toxicity by affecting the release of various neurotransmitters. Tat facilitates the exocytosis of excitatory neurotransmitters such as glutamate and NMDA and decreases the release of GABA, an inhibitory neurotransmitter, from the cortex and hippocampal neurons [114, 115]. Furthermore,Tat-mediated glutamate toxicity is exacerbated by phosphorylation of NMDA receptors.…”
Section: Role Of Hiv-1 Proteins In Neurotoxicitymentioning
confidence: 99%